Perinatal depression. Issue 3 (June 2021) - Lim, Grace
Abstract : Purpose of review: Perinatal depression is a common and debilitating complication of pregnancy and childbirth. Recent studies have elucidated relationships between acute birth events on depression risk, and novel treatments for postpartum depression have been discovered and approved. This article reviews current understandings about birth events on depression, new screening standards, and novel treatments for postpartum depression. Recent findings: Pain, analgesia, and depression are complex traits that are inter-related during and after pregnancy. Certain individuals may benefit more than others from addressing pain and suffering around childbirth. Exposures to general anesthesia or postdural puncture headache are associated with postpartum depression symptoms, although a causal relationship is unlikely. Brexanolone, ketamine and its related compounds, and nonpharmacologic options offer new or alternative therapies for depression, although safety information for some of these treatments in pregnancy and lactation are needed. Maternal health bundles call for close attention to perinatal mental health screening with validated instruments, and for timely treatment referrals in the 'fourth trimester'. Summary: Clinical monitoring and timely treatment of depression in the perinatal and postpartum periods is critical for maternal postpartum health and recovery. Perinatal specialists and researchers should continue to focus on tailored treatments specific to this special population.